Implementasi Kebijakan Pengelolaan Sampah Perkotaan Berbasis Masyarakat: Studi Pada Bank Sampah Unit Unyur Makmur Di Kecamatan Serang - Melvy Regitta Azahra; Riswanda Riswanda (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The issue of waste management, which continues to pose serious environmental challenges, remains a national concern in many regions, including the City of Serang. This study aims to analyze the implementation of community-based urban waste management policies through waste banks, referring to Serang City Regional Regulation Number 7 of 2021 on Waste Management. The research is driven by the persistence of illegal dumping sites, limited facilities and infrastructure for waste handling, and low public awareness that has not been adequately supported by socialization efforts or collaboration between private actors and relevant government agencies in Serang City. This study employs a descriptive qualitative method with a case study approach and draws on Charles O. Jones’s policy implementation theory. Data were collected through non-participant observation, semi-structured interviews, and documentation. The analysis followed the interactive model of Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of community-based waste management through waste banks has not yet operated effectively. Key contributing factors include limited human resources, insufficient budget allocation, and weak outreach efforts. The Environmental Agency (DLH) serves as the primary implementing body for waste management; however, stronger support from private institutions and community groups is needed to foster behavioral change and strengthen waste-management institutions at the local level.